2004
DOI: 10.1111/j.0906-6705.2004.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of formaldehyde induce DNA damage and delay DNA repair after UV irradiation in human skin cells

Abstract: Long-term occupational exposure to formaldehyde (FA) increases the risk for nasopharyngeal squamous cell carcinoma. As the skin is also in contact with FA by environmental exposure, we tested the genotoxic properties of appropriate low concentrations (<100 microM) of FA on cultured keratinocytes and fibroblasts of human skin. The initial DNA damage was assessed by comet assay. The induction of DNA protein crosslinks was measured by the ability of FA to reduce DNA migration induced by methyl-methane-sulfonate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…White blood cells or lymphocytes are the most frequently used cell type for Comet assay in human biomonitoring studies (reviewed by Angerer et al 2007;Faust et al 2004a, b;Moller 2006b); however, other cells have also been used, e.g., buccal cells (Szeto et al 2005), nasal (Mussali-Galante et al 2005), sperm (Delbes et al 2007;Fraser 2004;Schmid et al 2007;Singh et al 2003), epithelial (Graham-Evans et al 2004Emri et al 2004;Rojas et al 2000), and placental cells (Augustowska et al 2007).…”
Section: Comet Assay In Humansmentioning
confidence: 99%
“…White blood cells or lymphocytes are the most frequently used cell type for Comet assay in human biomonitoring studies (reviewed by Angerer et al 2007;Faust et al 2004a, b;Moller 2006b); however, other cells have also been used, e.g., buccal cells (Szeto et al 2005), nasal (Mussali-Galante et al 2005), sperm (Delbes et al 2007;Fraser 2004;Schmid et al 2007;Singh et al 2003), epithelial (Graham-Evans et al 2004Emri et al 2004;Rojas et al 2000), and placental cells (Augustowska et al 2007).…”
Section: Comet Assay In Humansmentioning
confidence: 99%
“…Some investigations suggest that DPCs kill cells based on the arrest of DNA and RNA synthesis at these "superbulky" adducts (8 -12). Therefore, the establishment of DPCs in an uncontrolled manner can prove lethal or perhaps mutagenic (13), whereas production of DPCs targeted to tumor cells can yield therapeutic benefit (14 -19).…”
mentioning
confidence: 99%
“…Previous studies suggested an interference of formaldehyde with the proper processing of various forms of DNA damage [22], [23]. In the case of global-genome NER activity, the detection of UV lesions depends on a specific accessory complex, known as UV-DDB (for UV-damaged DNA-binding), which consists of a damage sensor (DDB2) and a regulatory subunit (DDB1) [24].…”
Section: Introductionmentioning
confidence: 99%